CODE SWITCHING IN CULTURAL ADJUSTMENT PROCESSESAMONG THE JAVANESE - Ilya Nafila, - (2009)
This research tries to discover the code switching occurrences among the selected Javanese during their cultural adjustment processes in Bandung. This research is aimed to figure out the formulated research questions: (1) What types of code switching are identified among the selected Javanese during their cultural adjustment process?, (2) What are the functions of code switching are identified among the selected Javanese during their cultural adjustment process?, (3) What motivates the Javanese to code-switch? The present research used a qualitative method largely. In addition, the research used judgment sampling by taking some characteristics individual as the consideration of the sample selection. The respondents were ten Javanese students. They were five students of ITB, two students of UPI, and three students of IT Telkom. The data were collected through recording and interviewing sessions. The result establishes that all types of code switching were identified. The intra-sentential switching was found to be most frequently used one, followed by tag switching, and inter-sentential switching. Furthermore, the finding of the research reveals that only seven functions code switching were identified. Emphasis function was found to be most frequently used one, followed by interjections, personalization, untranslatability, reiteration, quotation, and clarification. Moreover, this research finds six motivations for Javanese students to code-switch: being accustomed to using Javanese, being accustomed to using Sundanese, adjusting to the listeners' language, conveying the message more expressively, having difficulties in finding the Indonesian words, and emphasizing the word.